2020
DOI: 10.1021/acs.joc.0c01249
|View full text |Cite
|
Sign up to set email alerts
|

Cyanomethyl Ether as an Orthogonal Participating Group for Stereoselective Synthesis of 1,2-trans-β-O-Glycosides

Abstract: Stereoselective formation of glycosidic linkages has been the prime focus for contemporary carbohydrate chemistry. Herein, we report cyanomethyl (CNMe) ether as an efficient and effective participating orthogonal protecting group for the stereoselective synthesis of 1,2-trans-β-O-glycosides. The participating group facilitated good to high β-selective glycosylation with a broad range of electron-rich and electron-deficient glycosyl acceptors. Detailed experimental and theoretical studies reveal the involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…The solvent was removed under reduced pressure and the residue was subjected to acetylation in 1 mL of dry CH 2 Cl 2 using Ac 2 O (45 μL, 0.48 mmol), Et 3 N (67 μL, 0.48 mmol) and catalytic amount of DMAP. After stirring over night at ambient temperature, usual workup and chromatographic purification gave 52 as a colorless oil, calculated yields are 41 % for 18β and 75 % for 30 ; 1 H NMR (400 MHz, CDCl 3 ): δ= 7.40–7.26 (m, 13H), 7.23–7.17 (m, 2H), 5.52 (d, J =4.9 Hz, 1H), 5.03 (t, J =8.6 Hz, 1H), 4.81 (dd, J =11.1, 3.8 Hz, 2H), 4.70 (d, J =11.4 Hz, 1H), 4.81 (dd, J =11.1, 3.8 Hz, 2H), 4.70 (d, J =11.4 Hz, 1H), 4.66 (d, J =12.2 Hz, 1H), 4.62– 4.54 (m, 3H), 4.46 (d, J =8.0 Hz, 1H), 4.30 (dd, J =4.9, 2.4 Hz, 1H), 4.21 (dd, J =8.0, 1.7 Hz, 1H), 4.08 (dd, J =11.2, 3.4 Hz, 1H), 3.97–3.92 (m, 1H), 3.78–3.61 (m, 5H), 3.53–3.47 (m, 1H), 2.04 (s, 3H), 1.53 (s, 3H), 1.45 (s, 3H), 1.34 (s, 3H), 1.33 (s, 3H); 13 C NMR (100 MHz, CDCl 3 ): δ= 169.8, 138.3, 138.2, 138.0, 128.4 (×3), 128.0, 127.9, 127.8 (×2), 127.7, 127.6, 109.3, 108.7, 101.8, 96.2, 82.8, 78.0, 75.2, 75.0 (×2), 73.5, 73.1, 71.3, 70.7, 70.6, 69.5, 68.7, 67.9, 26.1, 25.1, 24.3, 21.0; HRMS (ESI): calcd m/z for [M+Na] + for C 41 H 50 O 12 Na + 757.3194; Found 757.3196; the overall spectroscopic data are in complete agreement with assigned structures and consistent with literature [14] …”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The solvent was removed under reduced pressure and the residue was subjected to acetylation in 1 mL of dry CH 2 Cl 2 using Ac 2 O (45 μL, 0.48 mmol), Et 3 N (67 μL, 0.48 mmol) and catalytic amount of DMAP. After stirring over night at ambient temperature, usual workup and chromatographic purification gave 52 as a colorless oil, calculated yields are 41 % for 18β and 75 % for 30 ; 1 H NMR (400 MHz, CDCl 3 ): δ= 7.40–7.26 (m, 13H), 7.23–7.17 (m, 2H), 5.52 (d, J =4.9 Hz, 1H), 5.03 (t, J =8.6 Hz, 1H), 4.81 (dd, J =11.1, 3.8 Hz, 2H), 4.70 (d, J =11.4 Hz, 1H), 4.81 (dd, J =11.1, 3.8 Hz, 2H), 4.70 (d, J =11.4 Hz, 1H), 4.66 (d, J =12.2 Hz, 1H), 4.62– 4.54 (m, 3H), 4.46 (d, J =8.0 Hz, 1H), 4.30 (dd, J =4.9, 2.4 Hz, 1H), 4.21 (dd, J =8.0, 1.7 Hz, 1H), 4.08 (dd, J =11.2, 3.4 Hz, 1H), 3.97–3.92 (m, 1H), 3.78–3.61 (m, 5H), 3.53–3.47 (m, 1H), 2.04 (s, 3H), 1.53 (s, 3H), 1.45 (s, 3H), 1.34 (s, 3H), 1.33 (s, 3H); 13 C NMR (100 MHz, CDCl 3 ): δ= 169.8, 138.3, 138.2, 138.0, 128.4 (×3), 128.0, 127.9, 127.8 (×2), 127.7, 127.6, 109.3, 108.7, 101.8, 96.2, 82.8, 78.0, 75.2, 75.0 (×2), 73.5, 73.1, 71.3, 70.7, 70.6, 69.5, 68.7, 67.9, 26.1, 25.1, 24.3, 21.0; HRMS (ESI): calcd m/z for [M+Na] + for C 41 H 50 O 12 Na + 757.3194; Found 757.3196; the overall spectroscopic data are in complete agreement with assigned structures and consistent with literature [14] …”
Section: Methodssupporting
confidence: 82%
“…However, removal of the directing group necessitated several synthetic steps and harsh reaction conditions. To widen the scope of easily synthesizable and removable β‐directing methyl ether groups we have earlier reported cyanomethyl ether group on thioglycoside 1 c as a C2‐participating group wherein the π‐electrons of the nitrile group was instrumental in anomeric stabilization from α‐face to restrict the nucleophilic approach from the β‐face (Figure 1c) [14] . Despite the prominent stereodirecting effect of the C2‐substitution towards β‐glycosylation, the donor 1 c failed to deliver the β‐glycosides exclusively when reacted with various alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Molla et al (2020 ) reported efficient synthesis of 1,2- trans glycosides ( 41 ) using cyanomethyl ether protection at the C2 position of thioglycoside donors (VI in Scheme 5 ). The reactions of various 2-cyanomethyl ether protected thioglycosides ( 39 ) separately with various acceptors using NIS/TMSOTf at −40°C generated their corresponding glycosides ( 41 ) in moderate to very high yields and stereoselectivity.…”
Section: Techniques For 12- Trans Selective Glycos...mentioning
confidence: 99%
“…In continuation to our efforts to discover sustainable glycosylation methods, [26][27][28][29] we have recently reported cyanomethyl ether (CNMe) as a participating group for stereocontrolled trans-1,2-β-O-glycosylation when present at the C2-position of thioglycosides. During our earlier work a facile synthetic method for CNMe ether formation from C2-hydroxy allowed us to circumvent the well-documented difficulties of low yield and conversion associated with it.…”
Section: Introductionmentioning
confidence: 99%